(untitled) (Revista de História Regional, 2007)
The article describes how Celso Furtado envisages the regional problems of Northeastern Brazil, and seeks to demonstrate that such a perspective appears along with the construction and theorization of his very particular (sociological) structuralist conception of the economy. The text describes in detail the evolution and mutation of his ideas regarding Brazilian economic development in general and Northeastern regional issues in particualr, between 1958 and 1964. The article also examines the weight of his proposals, the economic evolution of the Northeast, and Furtado’s return to these problems in the eighties.